2021
DOI: 10.1177/1120700021995482
|View full text |Cite
|
Sign up to set email alerts
|

Migration behaviour of 2 clinically excellent cementless stems with different design rationales: 5-year follow-up of a randomised RSA-study

Abstract: Introduction: Excellent long-term survival has been reported for both the Taperloc and the Mallory-Head cementless stems. However, little is known about the migration behaviour of these stems which have different design rationales. The purpose of this randomised clinical trial was to compare the migration and clinical outcomes of these stems during 5 years of follow-up. Methods: 42 consecutive hips in 38 patients scheduled to receive cementless THA were randomised to either a Taperloc or a Mallory-Head stem. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This likely relates to the patients in that study being, on average, nearly a decade younger (mean age of 61 years) and healthier (mean BMI 27.8 kg/ m 2 ) in the paper by Nebergall et al 20 In larger samples of accepted dual-taper stems and uncemented acetabular components, the HHS and SF-36 PCS results appear to be at least equivalent. 21,23,28 While not definitive, this suggests that this device is a viable option for THA.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This likely relates to the patients in that study being, on average, nearly a decade younger (mean age of 61 years) and healthier (mean BMI 27.8 kg/ m 2 ) in the paper by Nebergall et al 20 In larger samples of accepted dual-taper stems and uncemented acetabular components, the HHS and SF-36 PCS results appear to be at least equivalent. 21,23,28 While not definitive, this suggests that this device is a viable option for THA.…”
Section: Discussionmentioning
confidence: 98%
“… 20 In larger samples of accepted dual-taper stems and uncemented acetabular components, the HHS and SF-36 PCS results appear to be at least equivalent. 21 , 23 , 28 While not definitive, this suggests that this device is a viable option for THA.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although external rotation of the femur during a fall is a common mechanism, not all PFF with rotational mechanism are caused by internal rotation of the stem relative to the femur and surgeons should ensure that the ACC and PCC are both minimised to increase likelihood of CCC during all rotational injuries. Given that following insertion cementless femoral stems may subside 1mm along the anatomical axis of the femur during normal function in the first three months following implantation (Van Der Voort et al, 2021), we recommend that surgeons should aim to reduce any gap between calcar and under surface of the stem collar to a maximum of 1mm to increase the likelihood of protection against early post-operative PFF.…”
Section: Discussionmentioning
confidence: 99%
“…However, this data is based on the combined Taperloc THA designs. A recent RSA study conducted with the Taperloc showed a subsidence of 1.12 mm (SD 2.12) and a retroversion of 0.33° (SD 1.36) ( 13 ). The type of Taperloc used in the study is not specified.…”
mentioning
confidence: 99%